Modeling an agent-based cooperative dynamic behavior in an uncertain context of SME's sustainable supply chain - Ben Mekki, Aicha; Tounsi, Jihene; Said, Lamjed Ben (2020 International Multi-Conference on: “Organization of Knowledge and Advanced Technologies” (OCTA), 2020)
by drawing upon the concept of competitiveness and the dynamism of the environment, a knowledge base model is developed to design the behavior of autonomous actors, having different objectives, within a group of cluster named Small and Medium Enterprises' (SMEs') located in different geographical area. The actors within these SMEs' must collaborate for the achievement of the cluster's objective. This later is influenced by sustainable responsibilities and should be ameliorate over an achievable set of constraints and parameters. In this work, a mechanism for monitoring and evaluation is needed to assess the SME's cluster performance. For that, we design a multiagent cooperative dynamic behavior as a dynamic multi-objective optimization (DMOP) problem and resort a modified dynamic multi-objective evolutionary method (M-DMOE) to choose a common solution for all actors, and then, the cluster's preferences are operated to determine the most suitable one (posterior).